Penerapan Perhitungan Langkah Harian Pada Pasien Penyakit Paru Obstruktif Kroni - Tambunan, Tresia Fransiska Ulianna; Nathania, Eugene; Tifany, Elisabeth Pauline (Majalah Kedokteran Indonesia, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a condition which airflow limitation occurs due to an abnormality of the airways. The cause of COPD is usually exposure to noxious particles or gases. COPD is often accompanied by metabolic syndrome and leads to impaired physical activity, leading to increased morbidity and mortality. According to the international recommendation, COPD patients should receive a 30-minute daily step program. Pulmonary rehabilitation program with daily step count could be prescribed to all COPD patients who have no exacerbations within 4 weeks and able to ambulate. The pedometer can be used for ≥ 8 hours/day, ≥ 3 days/week, and a minimum of ≥ 100 steps/day. Increasing activity that can be assessed by calculating daily steps in patients with COPD can reduce the number of exacerbations, reduces the risk of death, increases exercise capacity, and improves the quality of life.